Relationship of Knowledge with the Use of IUD Contraceptives at the Sako Health Center, Palembang in 2024 - Hernita, Teti; Virgian, Kharisma; Eprila, Eprila (Journal of Maternal and Child Health Sciences (JMCHS), 2024)
Background: Family development through increasing understanding and awareness of family functions. In the context of fostering resilience and welfare, families through fostering the sustainability of family planning participation are still faced with several problems, including the community not being optimally active family planning participants. The strategic target in accordance with the population and family planning development targets stated in the 2015-2019 RPJMN is to increase active family planning participants, namely increasing active family planning participants who use the Long-Term Contraceptive Method (MKJP). The types of long-term contraceptive methods are permanent contraception, implants, Intra Uterine Devices (IUDs). Factors that influence IUD use include age, education level, occupation, knowledge, parity. data obtained from the Sako Palembang Health Center from January to December 2023 as many as 6,695 active KB, with acceptors consisting of 105 MOW acceptors, 331 Condom acceptors, 760 IUD acceptors, 1,352 Implant acceptors, 1,518 Pill acceptors, 2,564 Injection acceptors. The purpose of this study was to determine the relationship between knowledge and the use of IUD KB at the Sako Health Center, Palembang in 2024. This study is an analytical survey study with a Cross Sectional approach. Where the study population is all active KB mothers who visit and use contraceptives at the Sako Palembang Health Center, starting from April to May 2024, totaling 40 people who were taken by accidental sampling. The study was conducted by guided interviews using questionnaires. The results of the univariate analysis of mothers who have good knowledge are 67.5% and those who are less good are 32.5%. The results of the Chi-Square test showed that there is a relationship between knowledge and the use of IUD contraception with a p value Key word: knowledge, IUD Contraceptives